Vitamin K1 and K2: Biochemistry, Clinical Significance, and Therapeutic Potential in Human Healt - Michał Wycik; Michał Szczupak; Anna Maria Modzelewska (Quality in Sport)
Vitamin K, encompassing phylloquinone (K1) and menaquinones (K2), is essential not only for coagulation but also for various extra-hepatic functions. This review summarizes current knowledge on the biological roles, absorption mechanisms, clinical relevance, and therapeutic implications of vitamins K1 and K2, with particular emphasis on their functions beyond hemostasis. The analysis is based on a comprehensive review of peer-reviewed articles, clinical trials, meta-analyses, and cohort studies sourced from databases including PubMed, Scopus, Web of Science, and Google Scholar. Keywords such as “vitamin K1,” “vitamin K2,” “menaquinone,” “osteocalcin,” “vascular calcification,” and “neuroprotection” guided the selection of the most relevant and up-to-date publications.